1997
DOI: 10.1152/jappl.1997.82.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface tension and intraluminal fluid on mechanics of small airways

Abstract: Airway constriction is accompanied by folding of the mucosa to form ridges that run axially along the inner surface of the airways. The mucosa has been modeled (R. K. Lambert. J. Appl. Physiol. 71:666-673, 1991) as a thin elastic layer with a finite bending stiffness, and the contribution of its bending stiffness to airway elastance has been computed. In this study, we extend that work by including surface tension and intraluminal fluid in the model. With surface tension, the pressure on the inner surface of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…The mechanics of this are similar to those for the initial buckling of the epithelial membrane (9), but, instead of the epithelial membrane, it is the entire thickness of the airway wall that is involved in the buckling. This buckling has been described by Hill and colleagues (6), who showed that it is governed by the mechanical and geometrical properties of not only the wall but also the parenchyma. They predicted that it could occur at a PL as low as 1 cmH 2 O.…”
Section: Discussionmentioning
confidence: 70%
“…The mechanics of this are similar to those for the initial buckling of the epithelial membrane (9), but, instead of the epithelial membrane, it is the entire thickness of the airway wall that is involved in the buckling. This buckling has been described by Hill and colleagues (6), who showed that it is governed by the mechanical and geometrical properties of not only the wall but also the parenchyma. They predicted that it could occur at a PL as low as 1 cmH 2 O.…”
Section: Discussionmentioning
confidence: 70%
“…Hill et al (1997) and Heil and White (2002) studied this fluid-solid model with particular focus on airways, but they did not account for the growth effect. Normalize the Cauchy stresses by s rr ¼ s rr =m s and s y y ¼ s y y =m s .…”
Section: Residual Stresses Induced By Growthmentioning
confidence: 99%
“…18 There have been many fluid mechanical models of the statics and dynamics of airway closure. 11,[19][20][21][22][23][24][25][26][27][28][29] Hammond 30 was one of the first to formulate a model to study the stability of an annular thin liquid film coating a rigid tube with circular cross section assuming a passive air-core phase. He found that waves initially amplified but eventually saturated into almost disconnected liquid collars.…”
Section: Introductionmentioning
confidence: 99%